2018
DOI: 10.1111/apt.14965
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: conditioned pain modulation in patients with the irritable bowel syndrome

Abstract: Conditioned pain modulation is significantly diminished in patients with IBS vs healthy controls. These data suggest that abnormal descending pathways may play an important pathophysiological role in IBS, which could represent an investigation and a therapeutic target in IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 78 publications
(114 reference statements)
2
25
0
Order By: Relevance
“…CPM/DNIC likely reflect the net balance between descending inhibitory and facilitatory signalling; hence, the study of DNIC in rodents represents a useful translatable measure linking pre‐clinical and clinical investigations (Bannister & Dickenson, ). Inefficient CPM might provide insight into underlying pathophysiological mechanisms, and disturbances have been reported in neuropathic pain, irritable bowel syndrome, cluster headache and fibromyalgia (Albusoda et al., ; Kosek & Hansson, ; Perrotta et al., ; Yarnitsky, Granot, & Granovsky, ). This proposal has also garnered support of mechanism‐led treatment of neuropathic patients as CPM efficiency inversely correlates with pain relief from tapentadol and duloxetine (Niesters et al., ; Yarnitsky, Granot, Nahman‐Averbuch, Khamaisi, & Granovsky, ).…”
Section: Introductionmentioning
confidence: 99%
“…CPM/DNIC likely reflect the net balance between descending inhibitory and facilitatory signalling; hence, the study of DNIC in rodents represents a useful translatable measure linking pre‐clinical and clinical investigations (Bannister & Dickenson, ). Inefficient CPM might provide insight into underlying pathophysiological mechanisms, and disturbances have been reported in neuropathic pain, irritable bowel syndrome, cluster headache and fibromyalgia (Albusoda et al., ; Kosek & Hansson, ; Perrotta et al., ; Yarnitsky, Granot, & Granovsky, ). This proposal has also garnered support of mechanism‐led treatment of neuropathic patients as CPM efficiency inversely correlates with pain relief from tapentadol and duloxetine (Niesters et al., ; Yarnitsky, Granot, Nahman‐Averbuch, Khamaisi, & Granovsky, ).…”
Section: Introductionmentioning
confidence: 99%
“…The CNS has the ability to modulate the intensity and perception of afferent nociceptive signals, via endogenous pain inhibitory pathways (known as "conditioned pain modulation") or excitatory pathways (known as "central sensitization") both on the spinal and supraspinal level [165]. The latest meta-analysis of 12 studies on conditioned pain modulation in IBS populations showed diminished conditioned pain modulation in IBS in comparison to HC with odds ratio of 4.84 (95%CI, 2.18-10.71, p<.0001) [4]. However 88% of all the study participants were female, whereas previous meta-analysis performed on males reported less deficiency in conditioned pain modulation [140].…”
Section: Visceral Pain Pathwaysmentioning
confidence: 99%
“…Heterotopic stimulation, i.e. the phenomenon of diminished pain perception due to application of another painful stimulus, has been widely applicated in the studies of visceral pain modulation [4]. Graham et al presented that in IBS, pain modulation by heterotopic stimulation acti-vated brain areas connected to bottom-up control such as amygdala or hippocampus, whereas in HC it activated areas of top-down control such as ACC, INS, PAG and RVM [78].…”
Section: Visceral Pain Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal and generalized somatic hypersensitivity and sensitization might be related to inflammatory and cognitive causes, among others. Indeed, endogenous pain modulation by the central nervous system (CNS) is abnormal in IBS and functional dyspepsia (FD), providing a plausible explanation for modified extra-GI sensory, autonomic, and GI neuronal function in FGID ( 15 20 ). To further examine the relationships between GI and extra-GI symptoms in FGID and underlying sensory function, sugar breath tests were used, which have been shown to evoke GI and extra-GI symptoms in patients with FGID ( 21 ).…”
Section: Introductionmentioning
confidence: 99%